2022
DOI: 10.1186/s12889-022-14432-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family structure on physical activity levels among children and adolescents in Western China in the era of COVID-19

Abstract: Purpose This study aimed to examine the levels of physical activity (PA) among children and adolescents in western China, and the influence of parents on their PA, in the era of coronavirus disease 2019 (COVID-19). Methods This cross-sectional study used a multistage questionnaire to evaluate 4800 children and adolescents of grades 4–12 (9–17 years old) from 48 primary and secondary schools across 16 districts and counties in western China. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A study encompassing all age groups demonstrated that family members in uence the interaction between medical staff and patients approximately 65% of the time [14]. Considering the relatively diverse range of family structures prevalent in our country, ranging from nuclear families to three-generation households and intergenerational families [15], coupled with a society experiencing declining birth rates, pediatricians nd themselves not only healing children but also addressing familial issues spanning multiple generations. This distinctive patient population combined with being part of a group practice makes pediatricians more susceptible to con icts arising from doctor-patient interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A study encompassing all age groups demonstrated that family members in uence the interaction between medical staff and patients approximately 65% of the time [14]. Considering the relatively diverse range of family structures prevalent in our country, ranging from nuclear families to three-generation households and intergenerational families [15], coupled with a society experiencing declining birth rates, pediatricians nd themselves not only healing children but also addressing familial issues spanning multiple generations. This distinctive patient population combined with being part of a group practice makes pediatricians more susceptible to con icts arising from doctor-patient interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The physical activity survey was conducted using the International Physical Activity Scale (IPAQ) short form, which is commonly used internationally [ 20 ]. The questionnaire has been widely adopted among Chinese youth [ 21 , 22 ]. The IPAQ short form consists of 7 main entries that investigate the number of times participants engaged in physical activities of different intensities in the past 7 days and the average duration of each.…”
Section: Methodsmentioning
confidence: 99%
“…The physical activity survey was conducted using the International Physical Activity Scale (IPAQ) short form, which is commonly used internationally [20]. The summary table has been widely adopted among Chinese youth [21,22]. The IPAQ short form consists of 7 main entries that investigate the number of times participants engaged in physical activities of different intensities in the past 7 days and the average duration of each.…”
Section: Physical Activitymentioning
confidence: 99%